COMPERATIVE ANALYSIS: performance and possibility of bankrupt in banking sector of Finland, China and Bangladesh. - Aktaruzzaman, Md (My University, 2019)
The purpose of this thesis is to study and compare bank performance, bank profitability and the possibility of bankrupt in the banking sector of selected three countries such as Finland, China and Bangladesh. Especially the study makes a valid comparison of the banking sector of these countries. The research problem can be stated in two sentences. Firstly, in comparison with Finland and China, what are the key financial factors that are lagging in the banking sectors of Bangladesh behind? Secondly, What are the strengths of banking sectors of Bangladesh in comparison with China and Finland that can be a big opportunity for Bangladesh? This study is based on the Finnish, Chinese and Bangladeshi bank data acquired from Bank Scope database and Fitch Connect Data Services(FCDS), also foreign banks from selected countries which are considered in the sample section. The goal of this study is on large and systemically important banks from which sufficient data is available.The chosen sample criteria are different from one country to another. The sample periods are 2000 to 2017. The methods of the study is panel regression, more specially OLS regression and correlation matrix are estimated to measure profitability, and Altman-Z score is calculated to evaluate the possibility of bankrupt. Furthermore, it is important to know the strength of banking sector of an economy. This study also provides more details about overview of the financial sector, description of the controlling authorities, nature of the economies of these three countries. The results of the study show that most of the variables chosen for the panel regression explain bank profitability and variable taken for the Altman-Z score measures the chance of bankrupt. Among three countries Bangladeshi banking sector is the least favourable position than Finnish & Chinese banking sector because Bangladeshi banking sector is considered an inefficient market and different market regulation than others. The profitability indicator like return of assets (ROA) and return on equity (ROE) in banking sector of Bangladesh fluctuates more than of other two countries. In addition, The banking sector of Bangladesh generates lower share of income, which is linked to lower profitability and higher liquidity risks than Finnish and Chinese banking sector. The bank’s business growth do not explain bank profitability in Bangladesh. But during global financial crisis Bangladesh was the least affected countries among others. China is the largest economy in terms of GDP and technologically advanced. Moreover, Service sector plays an important role for both Finnish and Chinese banking industries.
Keywords: Bank Performance; profitability; Bankrupt; Altman-Z score; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|